2008
DOI: 10.1016/j.engfracmech.2007.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling and analysis of crack shape evolution in mode-I fatigue Middle Cracked Tension specimens

Abstract: A numerical procedure was employed to study the shape evolution of fatigue cracks in Middle Cracked Tension specimens. This iterative procedure consists of a 3D finite element analysis to obtain the displacement field in the cracked body, calculation of stress intensity factors along crack front and definition of local crack advances considering the Paris law. Numerical predictions were compared with experimental crack shapes with a good agreement. The evolution of crack shape was analysed for different propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…These coordinates were directly used to define the initial crack on the FEM model. All numerical variables were fixed taking into consideration previous optimization studies [7,8]. A set of independent numerical propagations was carried out, with values of m between 1 and 5, with constant increments of 0.25.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These coordinates were directly used to define the initial crack on the FEM model. All numerical variables were fixed taking into consideration previous optimization studies [7,8]. A set of independent numerical propagations was carried out, with values of m between 1 and 5, with constant increments of 0.25.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
“…Two main groups of parameters can be distinguished: global parameters which quantify the shape of all crack and local parameters which study the behaviour of few specific nodes [7,8]. Herein, it was used a global parameter (Z) given by the ratio A 1 /A 2 , where A 1 and A 2 are, respectively, the light and dark areas shown in Fig.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee and Lee [20] investigated fatigue crack growth in single side repairs aluminium plate. Branco et al [21] used these techniques to evaluate the curvature of the crack front. They found that and stable crack curvature was achieved independently from the starting shape.…”
Section: Introductionmentioning
confidence: 99%